1987
DOI: 10.1063/1.866373
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian turbulence and spatial complexity in a Stokes flow

Abstract: A simple Stokes flow problem, corresponding to an incompressible flow between two eccentric cylinders rotating alternately, is investigated numerically. It is demonstrated that for a wide range of system parameters the fluid particles can evolve along highly chaotic orbits, thereby providing an example of so called ‘‘Lagrangian turbulence.’’ Passive scalar distributions can rapidly evolve into structures of remarkable spatial complexity that can be characterized in terms of the underlying phase space dynamics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 13 publications
2
40
0
Order By: Relevance
“…For example, Aref & Balachandar (1986) showed that unsteady Stokes flow between eccentric rotating cylinders, in which the rotation rate is modulated periodically in time, can exhibit chaotic particle motions of the Smale horseshoe type, Thus this particular Stokes flow is effectively non-reversible. This same flow has also been studied experimentally as well as theoretically by Chaiken et al (1986Chaiken et al ( , 1987. Ottino and coworkers (see Chien, Rising & Ottino 1986; Khakar, Rising ) studied chaotic fluid particle motions in a variety of flows, both at small and large Reynolds numbers with particular emphasis on using dynamical systems techniques as a theoretical basis for the discussion of mixing processes.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Aref & Balachandar (1986) showed that unsteady Stokes flow between eccentric rotating cylinders, in which the rotation rate is modulated periodically in time, can exhibit chaotic particle motions of the Smale horseshoe type, Thus this particular Stokes flow is effectively non-reversible. This same flow has also been studied experimentally as well as theoretically by Chaiken et al (1986Chaiken et al ( , 1987. Ottino and coworkers (see Chien, Rising & Ottino 1986; Khakar, Rising ) studied chaotic fluid particle motions in a variety of flows, both at small and large Reynolds numbers with particular emphasis on using dynamical systems techniques as a theoretical basis for the discussion of mixing processes.…”
Section: Introductionmentioning
confidence: 98%
“…There are no internal stagnation points. In this sense, the MHD flow in the gap between two eccentric cylinders is topologically different from the shear-flow induced when the inner cylinder rotates as in Aref & Balachandar (1986) and Chaiken et al (1987).…”
Section: Mhd Flow Between Two Eccentric Cylindersmentioning
confidence: 99%
“…This approximation is commonly used in the context of Stokes flows (i.e. Landau & Lifshitz 1959, p. 91;Aref & Balachander 1986;Chaiken et al 1987).…”
Section: Two Point Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The approximation is commonly used in the context of Stokes flows and chaotic advection. 15,16 When the potential difference is induced across electrode group A n -C, we denote the resulting flow field as n ͓Eq. ͑10͔͒.…”
Section: Time-modulated Flowsmentioning
confidence: 99%